The lichen biota of the Special Area of Conservation Rio Pentemina (Ligurian Apennines, N Italy) - Giordani, Paolo; Canali, Giulia; Di Nuzzo, Luca; Gheza, Gabriele; Bianchi, Elisabetta; Di Natale, Stefano; Mayrhofer, Helmut; Benesperi, Renato; Nascimbene, Juri (Natural History Sciences, 2025)
Despite its restricted geographical extent, Liguria hosts a very rich lichen biota. Nevertheless, the lichenological exploration of Liguria remains highly fragmented, both in space and time. Indeed, there are only a handful of comprehensive lichen biota lists for specific areas of Liguria. To address this gap of knowledge and support broader biodiversity, taxonomic, and ecological studies, we present a list of the lichen biota of the Pentemina Valley, which we consider to be one of the most interesting areas in the Ligurian Apennines from a lichenological point of view. The list includes 200 infrageneric taxa, fourteen of which are new to Liguria (e.g., Loxospora elatina). Additionally, fourteen other species of conservation interest have been collected (e.g., Buellia hyperbolica), while many others have been recorded after a century or more since the first and, in some cases, only report (e.g., Ochrolechia szatalaensis or Verrucaria papillosa).
Keywords: Biodiversity; epilithic; epiphytes; lichens; terricolous